Residual phosphorus is a significant pool in soil phosphorus cycling - Yli-Halla, Markku; Uusitalo, Risto (Scientific Agricultural Society of Finland, 2026)
Sequential phosphorus (P) fractionation schemes are widely used to characterize soil P pools, yet the most chemically resistant forms are often omitted in modern applications of fractionations. We quantified inorganic and organic P in ten predominantly clayic or fine sandy acidic agricultural soils from SW Finland, paying special attention to the residual P not recovered in the four common extractions of Chang-Jackson scheme (NH₄Cl-, NH₄F-, NaOH-, and H₂SO₄-extractable P). Total P (H2SO4-H2O2-HF) ranged from 1148 to 2467 mg kg⁻¹, with organic P constituting 15–49%. The four inorganic fractions represented on average 43% of total P. A substantial residual P pool (304–474 mg kg⁻¹) accounted for 25% of total P and 32–42% of inorganic P, exceeding the size of any individual P fraction. Our results suggest that routine fractionation may substantially underestimate soil inorganic P reserves and oversimplify our view on long-term P dynamics. This has implications for long-term P budgets and P availability under fluctuating redox conditions, including erosion-mediated P losses.
Keywords: agricultural soils; inorganic P; P fractionation; residual P; total P